2021
DOI: 10.3390/diagnostics11010070
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI Assessment of Thalamic Structural Changes in Earthquake Survivors

Abstract: Moving from the central role of the thalamus in the integration of inner and external stimuli and in the implementation of a stress-related response, the objective of the present study was to investigate the presence of any MRI structural and volumetric changes of the thalamic structures in earthquake witnesses. Forty-one subjects were included, namely 18 university students belonging to the experimental earthquake-exposed group (8 males and 10 females, mean age 24.5 ± 1.8 years) and a control group of 23 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Despite multiple strands of evidence that traumatic events can affect the structure and function of the thalamus, this region is rarely included as an ROI in a priori studies of CA. After traumatic events in adulthood, structural and functional changes have been observed in the thalamus [ 28 30 ]. Thalamic structural deviations after CA have also been observed [ 31 , 32 ], and CT has been associated with functional hyperconnectivity of the thalamus in a transdiagnostic sample [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple strands of evidence that traumatic events can affect the structure and function of the thalamus, this region is rarely included as an ROI in a priori studies of CA. After traumatic events in adulthood, structural and functional changes have been observed in the thalamus [ 28 30 ]. Thalamic structural deviations after CA have also been observed [ 31 , 32 ], and CT has been associated with functional hyperconnectivity of the thalamus in a transdiagnostic sample [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple strands of evidence that traumatic events can affect the structure and function of the thalamus, this region is rarely included as an ROI in a priori studies of CA. After traumatic events in adulthood, structural and functional changes have been observed in the thalamus (28-30). Thalamic structural deviations after CA have also been observed (31, 32), and childhood trauma has been associated with functional hyperconnectivity of the thalamus in a transdiagnostic sample (33).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown structural changes in the thalamus after trauma or severe stress ( 6 , 14 ). Changes in thalamic volume have been observed in victims of childhood maltreatment or earthquakes ( 15 , 16 ). The thalamus consists of various nuclei, each of which has a distinct location and function.…”
Section: Introductionmentioning
confidence: 99%